Risk factors affecting the mental health of first-year university students on a health sciences campus and related factors - EROL, SAİME; GÜR, KAMER; ÇALIK, KEVSER BURCU; UZUNER, ARZU; KARACA, SEMRA; APAYDIN KAYA, MEMNUNE ÇİĞDEM (My University, 2022)
PurposeThe purpose of this study is to determine the mental health status and risk factors for the mental health of first-year university students on a health sciences campus. Design/methodology/approachThis is a descriptive study. The research was conducted with first-year students in the health sciences, dentistry and medical faculties of a state university (n = 770). The data were collected with a sociodemographic questionnaire, the Risk Behavior of Young Adults Survey, the Bergen Insomnia Scale, General Health Questionnaire-28 and the Mental Health Improvement Scale. Body mass index was calculated. FindingsAmong the students, 53.7% experienced feelings of hopelessness in the last year and 1% had attempted suicide. The percentage of students found to be at risk in terms of mental health was 41.9%; 39.4% reported that they suffered from insomnia. It was found that those who had been subjected to bullying, felt hopelessness, had suicidal thoughts, planned to commit suicide and students who experienced sleeping problems were more at risk in terms of psychological issues (p < 0.01). Insomnia (beta: 3.341) and smoking (beta: 2.226) were identified as the strongest risk factors for mental health in first-year health sciences students (p < 0.005). Practical implicationsThe results of the research offer an opportunity to get to know the characteristics of first-year university students who are at risk for mental health. It offers the opportunity to closely monitor and protect the mental health of students starting from the first grade. Originality/valueIn this study, it was determined that approximately half of the first-year university students were in the risk group in terms of mental health. Female gender, having a chronic illness, smoking a day or more in the past 30 days, not doing any physical activity, having a weak BMI, being bullied in the past 12 months, being cyberbullied in the past 12 months and having insomnia have been identified as risk factors that negatively affect mental health.
Keywords: Sağlık Bilimleri; Health Sciences; Psikiyatri; Klinik Tıp (MED); PSYCHIATRY; Clinical Medicine (MED); Psikiyatrik Ruh Sağlığı; Psikiyatri ve Ruh Sağlığı; Psychiatric Mental Health; Psychiatry and Mental Health; University first-year student; Mental health; Insomnia; Risk behavior; General health; SELF-EFFICACY; PREVALENCE; DISORDERS; SYMPTOMS; INSOMNIA; SCALE